Koncepcja ruchu w dyskursie o tańcu współczesnym - Pędzisz, Joanna (Acta Neophilologica, 2020)
The aim of the considerations presented in this paper is to determine the specificity of movement in contemporary dance. This specificity is considered at three levels: as the relationship of body parts to each other, as the relation of the body and part of it to the stage space, and as the relation of the body and parts of it to the qualitative parameters of movement such as speed, tension and size. The research data consist of the descriptions of dance performances, which are published in printed or electronic form during the organization of conferences, meetings and dance theatre festivals.